SYSTEM AND METHODS FOR DETECTION OF SUBJECTS VITALS AND PHYSIOLOGICAL SYMPTOMS VIA NON-CONTACT METHODS - RAMPRAKASH Vikram; HOLDEN Dave; SATING Richard; BALOUGH Ken (2024)
The present invention provides a non-contact vital signs monitoring that correctly detects vital signs of the subject by correcting the signals measured by reflectance and distance variations between measurements. The present invention provides a number and type of sensors suitable for correctly monitoring vital signs and physiological signals of a subject. Certain aspects of the invention include the use of signal scoring methods. In such embodiments, the acquired data and/or information is used to score a signal acquired from a non-contact vital monitoring that aids the accurate measurement of various vital signs of a subject, including, without limitation, a subject 's temperature and cardiovascular and respiratory information. The present invention provides a viable solution for monitoring vital signs without remote contact that overcomes the deficiencies of existing solutions known in the art. La presente invención proporciona un monitoreo de signos vitales sin contacto que detecta correctamente los signos vitales del sujeto corrigiendo las señales medidas por reflectancia y variaciones de distancia entre mediciones. La presente invención proporciona un número y un tipo de sensores adecuados para monitorear correctamente los signos vitales y las señales fisiológicas de un sujeto. Ciertos aspectos de la invención incluyen el uso de métodos de puntuación de señales. En tales modalidades, los datos y/o la información adquiridos se utilizan para puntuar una señal adquirida a partir de un monitoreo vital sin contacto que ayuda a la medición precisa de diversas constantes vitales de un sujeto, incluyendo, sin límite, la temperatura de un sujeto y la información cardiovascular y respiratoria. La presente invención proporciona una solución viable para el monitoreo de signos vitales sin contacto a distancia que supera las deficiencias de las soluciones existentes conocidas en la técnica.